FACTORS FORMING ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) OF EMPLOYEE IN AN ORGANIZATION - Ni Wayan Mujiati (Forum Manajemen STIMI Handayani Denpasar, 2015)
As a global era, the 21 st century has been responsible for the dramaticchange taking place in organizations. On one hand, its has threatened both publicand personal organization; on the other hand, it has created opportunities for them.The opportunities to develop within organizations, to develop career, and to bepaid in accordance with their smart performance and positive attitude toward theirorganization are the indicators showing their organization citizen behavior (OCB)in their organization. This present study discusses the definition of OCB, the motivemotivating it and the factor forming the OCB ofemployee in their organization.